FAKTOR-FAKTOR YANG MEMPENGARUHI LAMANYA PENYELESAIAN AUDIT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ignes Januar Cahyadi (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
Audit report lag refers to the number of days from the company’s year end (fiscal year) to the audit report date. The objective of this study is to investigate the influence of the gearing ratio, profitability, liquidity, firmsize, firm age and leverage toward the audit report lag. The population of this study is all the manufacturing companies listed in Indonesia Stock Exchange during 2008 until 2011. Samples of manufacturing companiesselected from purposive sampling method. The statistic method used to test on the research hypothesis is multiple regression method. The conclusion of this research is that the gearing ratio, liquidity and firm size have influence towards audit report lag. Profitability, firm age and leverage do not have any influence towards audit report lag. The finding show that the gearing ratio has a positive relation with the audit report lag. While liquidity and firm size have a negative relation with the audit report lag.